2014
DOI: 10.1080/00405000.2014.930576
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide sol-containing diallylmethyl alkyl quaternary ammonium salt synthesized by sol–gel process: characterization and properties

Abstract: Zinc oxide sols-containing quaternary ammonium bromide compounds, including diallylmethyl dodecyl/tetradecyl/ hexadecyl/octadecyl ammonium bromide, were synthesized from zinc acetate and quaternary ammonium bromide compounds via sol-gel process. Effects of alkyl chain length and double allyl of quaternary ammonium salts on the stability of the sols were investigated. The sols were characterized by X-ray diffraction. Morphologies of the sols were observed with transmission electron microscopy. The various zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…BAC gathered the attention of the scientific community because of its physical–chemical characteristics [ 26 ] and its mechanisms of interaction with bacteria [ 27 ], later discussed in the Results and Discussion section of the present paper. Several studies regarding the immobilization of QAC compounds in nanostructured material were published [ 22 ], including the functionalization of metal oxide nanoparticles [ 28 , 29 ]. However, none of those cases include the functionalization of macroscopic metal oxide pellets.…”
Section: Introductionmentioning
confidence: 99%
“…BAC gathered the attention of the scientific community because of its physical–chemical characteristics [ 26 ] and its mechanisms of interaction with bacteria [ 27 ], later discussed in the Results and Discussion section of the present paper. Several studies regarding the immobilization of QAC compounds in nanostructured material were published [ 22 ], including the functionalization of metal oxide nanoparticles [ 28 , 29 ]. However, none of those cases include the functionalization of macroscopic metal oxide pellets.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Dimethylammonium ethyl methacrylate (DM) is amine basic; the molecule contains a tertiary amino group, an ester group, and an unsaturated double bond, and acid can produce salt and chloromethane and other reactions to produce quaternary ammonium ionic liquids (DM x ). 47,48 Taking inspiration from the alkylamines in the natural antibacterial purple daisy, we synthesized a series of antibacterial hydrogels based on DM x (X = 2, 6, 12, and 16) with different chain lengths. The effect of the length of the hydrophobic alkyl group on the antimicrobial activity of DM x and on the mechanical properties of the aniline spheretoughened hydrogel as well as the effect of the aniline sphere content on the conductivity of the hydrogel were investigated in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the emergence of antimicrobial materials offers great hope for solving the problem of infection risk. For example, cationic polyelectrolyte brushes grafted from bacterial cellulose (BC) nanofibers were introduced into a polydopamine/polyacrylamide hydrogel by Yang et al, and the hydrogel showed less inflammatory response and a faster healing rate in wound healing in rats in vivo . The preparation methods for the binding of antimicrobial agents to hydrogels mainly include physical binding (direct encapsulation, solubilization and diffusion, carrier encapsulation) and chemical binding (formation of chemical bonds between hydrogels with inherent antimicrobial activity). , Amines are widely present in the biological world, with very important physiological and biological activities; for example, alkaloids, nucleic acids, antibiotics, and proteins are amine derivatives, and most of the drugs are amines or amine derivatives, so mastering the nature and synthesis of amines is the basis of the study of these complex natural products and the better maintenance of human health. , Dimethylammonium ethyl methacrylate (DM) is amine basic; the molecule contains a tertiary amino group, an ester group, and an unsaturated double bond, and acid can produce salt and chloromethane and other reactions to produce quaternary ammonium ionic liquids (DM x ). , Taking inspiration from the alkylamines in the natural antibacterial purple daisy, we synthesized a series of antibacterial hydrogels based on DM x ( X = 2, 6, 12, and 16) with different chain lengths. The effect of the length of the hydrophobic alkyl group on the antimicrobial activity of DM x and on the mechanical properties of the aniline sphere-toughened hydrogel as well as the effect of the aniline sphere content on the conductivity of the hydrogel were investigated in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…As long-acting antibacterial agents, quaternary ammonium compounds have been used to modify ZnO NPs to enhance their antibacterial activity. [28] Mascia et al prepared ZnO NPs in situ within polyethyleneimine (PEI) matrix following blended them with zein to produce zeinmodified fibers by electrospinning, and the antibacterial activity and mechanical property of the composite zein fibers were significantly improved. [29] Hui et al incorporated quaternary ammonium chitooligosaccharides into ZnO/palygorskite nanocomposites which showed good synergistic antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%